The Application of Anaerobic Plastic Media Biofilter for Removal of Ammonia and Oil and Grease in Slaughterhouse Wastewater - Vera Viena; Suarni Suarni; Irda Yunita (Serambi Journal of Agricultural Technology, 2021)
Slaughterhouse wastewater generally contains organic substances, fatty oils and ammonia which can cause pollution to the environment. This study aims to analyze the removal efficiency of ammonia, oil and grease and pH of the slaughterhouse wastewater from Banda Aceh using an anaerobic biofilter. The bioreactor was acclimatized for 30 days to form a biofilm layer before being used as a biofilter. The results showed a decrease in the oil and grease content and pH of the slaughterhouse wastewater after given 6 days contacted time. Ammonia parameter increased by 2.02%, while the efficiency of oil and grease and pH also increased by 96.667% and 30.927%, respectively. It can be concluded that the anaerobic plastic media biofilter has been able to reduce the oil grease content and pH of slaughterhouse below the quality standard, except for ammonia which exceeds the quality standard of Environmental Government Regulation no. 5 of 2014.